QLPV modelling of helicopter dynamics. Issue 28 (2019) - Panza, Simone; Viganó, Luca; Gobbo, Diego Del; Lovera, Marco
Abstract: Linear Parameter Varying (LPV) modelling has been studied in aeronautics for a long time as a means to formulate gain-scheduling problems in a systematic way, in terms of number of involved parameters and interpolation points. In this paper the development of a quasi-LPV (qLPV) or "stitched" model for helicopter dynamics is presented and discussed, with specific reference to two problems. First, selecting suitable flight dynamics identification and control law design points to minimize the number of experimental flights necessary for design and validation of control laws. Second, highlighting the flight conditions that are potentially critical from the perspective of closed-loop stability and performance.